Smooth Dearomatization of Some Phenols by BAIB and Facile Aerial Oxidation of Two γ-Hydrogen Containing Anthraquinones - Roy, H N; Roy, Pijush K; Shumi, SA; Rahman, MM; Islam, MN (Journal of the Bangladesh Chemical Society, 2012)
At ambient condition bis(acetoxy)iodo benzene (BAIB) oxidized phenol and substituted phenols and the oxidized products undergo easy annulation reaction with cyanophthalide at ice cold temperature. Methyl or ethyl group at position C-1 in anthraquinone system has participated smooth aerial oxidation under sunlight. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11767 Journal of Bangladesh Chemical Society, Vol. 25(1), 21-29, 2012